External injection into JINR phasotron – computer simulation III - Onischenko, L.M.; Samsonov, E.V. (Вопросы атомной науки и техники, 2001)
Computer simulation of the beam dynamics is reported for the external injection into the JINR Phasotron of the preliminary bunched 5 Mev beam. The capture efficiency is found to be 65.5% and not too much dependent on the scattering by the foil.